The perception of HIV / AIDS : the case of infected Malay women at Rumah Solehah, Cheras, Kuala Lumpur - Naimah binti Ismail (Kulliyyah of Islamic ReveaIed Knowledge, International Islamic University Malaysia, 2007)
This is a qualitative study on the perceptions of HIV-infected Malay women at Rumah Solehah, Cheras, Kuala Lumpur towards HIV/AIDS. The objectives of the study are to examine the socioeconomic backgrounds of HIV-infected Malay women, their perception of HIV/AIDS, and the impact of the illness on their lives. The study was carried out from February to May 2005. The sample of this study consists of eight HIV-positive women. In-depth interview, participant observation and library research were the methods used in the process of collecting data. The topics discussed surrounding their life before HIV infection, during the early period of diagnosis and after the diagnosis of HIV. Interesting to note that in this study many of the informants interviewed were from lower academic achievement, came from broken family, had intravenous drug user partners and had been involved in lifestyles with a high risk of contracting HIV infection. In the issue of knowledge, the women had little knowledge about of HIV/AIDS. In addition, the findings also show that the HIV-infected Malay women perceive HIV/AIDS like other common illnesses that are caused by a virus and refuted the negative perception associated with the disease. Having the virus in the body also caused life-altering consequences in their lives. They include declining physical and emotional health, lost of economic resources and waning social relationship. However, being HIV-positive has proven to be a turning point in most of the women’s lives. The illness is perceived as a motive to change their behaviour and to see life in a new perspective.